The Problems of Notions in Eschatology - Smentek, Izabella (Teologia w Polsce, 2020)
The present article deals with the use and understanding of eschatological terminology. The concepts used and the starting point of the consideration affect its orientation and the distribution of aspects. If we take the “final events” as a starting point, we obtain an anthropological picture of man’s fate and his destiny to eternity. When starting with the mystery of God and His plan, one must pay attention to the Person of Christ the Coming One and this makes eschatology a treatise on the Triune God that completes His work. This study also draws attention to the semantic nuances of some notions relating to eternal life, such as novelty, kingdom, Father’s house, heaven, glory or eternal happiness. These and other expressions contain a wealth of meaning rooted in Revelation and the Church’s tradition. Their thoughtful and conscious use serves the purpose of a deep and creative and at the same time precise reflection.